(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
Effluent and its receiving sediment samples were collected on seasonal basis, comprising of three months (August to October, 2014) in the wet season and three months (December 2014 to February 2015) in the dry season. Five sampling points around the lubricating oil company were marked for the study. Physicochemical parameters of the effluent samples such as pH, temperature, conductivity, total dissolve solids were determined in situ. Dissolved oxygen and biochemical oxygen demand were determined by Winkler´s method. Digestion of the sediments was carried out by acid dissolution. The heavy metals (Mn, Ni, Co, Cd and Pb) level was determined using Flame Atomic Absorption Spectrophotometer. The results revealed that the physicochemical parameters ranged between (27.40 to 29.860C) for temperature, pH (6.89 to 7.88), electrical conductivity (92.27 to 292.84µs/cm), total dissolve solids, dissolved oxygen (2.58 to 7.01mg/L), biochemical oxygen demand (5.00 to 14.00mg/L) for the sampling periods. The overall total metal was in similar order: Mn > Ni > Co > Cd > Pb for both seasons. Most of the results were within the recommended limit required except for the levels of biochemical oxygen demand which exceeded the recommended value of 10mg/L in dry season by WHO, (2006). Statistically, no significant difference at p ≤ 0.05 between the parameters obtained in both seasons. The study concluded that the effluents discharged from the lubricating oil company in osogbo was polluted based on the results of biochemical oxygen demand and the Cd concentrations in the sediment samples.